Forced Marriage Following Khalwat (Margandak) from the Perspective of Islamic Family Law: A Case Study of Huta Raja Lama Village - Emlia Fasia Siregar; Ramadhan Syahmedi Siregar (Lambung Mangkurat Law Journal, 2025)
This study examines the practice of forced marriage following khalwat (margandak) that persists in Huta Raja Lama Village, Padang Lawas Regency. The practice is driven by the view that couples caught in khalwat should be married immediately to preserve family honor and avoid public shame. The research analyzes this phenomenon from the perspective of Islamic family law in Indonesia. Adopting a socio-legal qualitative (empirical) approach, the study employs in-depth interviews with customary leaders, religious leaders, families, and village officials, complemented by field observation and document analysis. Informants were selected in stages—beginning with relevant key informants and then expanding through referrals—and the data were thematically analyzed, with reliability supported by corroboration across interviews, observations, and documents. The findings indicate that forced marriage continues due to strong socio-cultural pressures—such as preserving honor, concealing shame, and adherence to customary norms—and is framed as a moral obligation of the family to restore reputation. However, the practice is misaligned with the principles of Islamic family law and fiqh, as it generates psychological pressure, proceeds without genuine consent, and contravenes the voluntariness requirement stipulated in Article 6 of Law No. 1/1974 (as amended by Law No. 16/2019) and the Compilation of Islamic Law (KHI). It also creates social harms and vulnerabilities in civil rights when marriages are not officially registered.